Intracellular serine protease 1 of Bacillus subtilis is formed in vivo as an unprocessed, active protease in stationary cells. - Sheehan, S M (1990)
Western immunoblots and assays of Bacillus subtilis extracts showed that intracellular serine protease 1 is produced in a form larger than previously reported, appears not to have undergone N-terminal processing, and is active in the presence or absence of calcium. No evidence for an inactive precursor form of the protease was found.